"Abba" revisited: merging the horizons of history and rhetoric through the new rhetoric structure for metaphors - S. Tsang (Acta Theologica)
This study uses the “Abba” metaphor to demonstrate the New Rhetoric model of metaphor as a tool to understand Paul’s rhetorical purpose in using metaphors. By looking closely at the theme (i.e., the idea the author tries to convey) and phoros (i.e., the picture the author uses to convey the idea). From a historical perspective, the “Abba” metaphor used in Galatians 4:6 can be linked to Palestinian origins. At the time of writing of the Letter to the Galatians, “Abba” had already been ingrained firmly in the Galatian Christian community. Paul used the metaphor to attack the agitators by excluding them from the spiritual familia of Jesus. In this recipient-oriented reading, it is shown that Paul used the metaphor to exhort with great urgency those on the fringe to return to the fold. In this way it is illustrated that, by using the approach of the New Rhetoric in describing a metaphor, an interpreter can raise questions on both the understanding of the author and readers, as part of the communication process.